EFEKTIVITAS PENEGAKAN HUKUM CYBER MELALUI SURAT EDARAN KAPOLRI NO. SE/2/II/2021 DALAM MENANGANI BERITA HOAKS - Dani Satriana; Deny Haspada (Iustitia Omnibus (Jurnal Ilmu Hukum), 2022)
The background of the National Police Chief General Listyo Sigi Prabowo issued a Circular (SE), SE/2/II/2021 relating to the ITE Law No. 19 of 2016 is to anticipate hoax news circulating in the community through cyber media. The circular contains eleven points, including asking police investigators to prioritize restorative justice in resolving cases by prioritizing peaceful steps in resolving cases related to reports of alleged violations of the ITE Law. The problems of this research focus on two questions, namely: (1) How is the effectiveness of cyber law enforcement in dealing with hoax news? (2) How to implement the circular letter of the National Police Chief No. SE/2/II/2021 related to UU ITE? This study uses a normative juridical method with a Sociology study approach of law. The research specifications, namely theories, concepts, legal principles and legal regulations related to hoax news based on SE Chief of Police No. SE/2/II/2021. Based on this study, it can be concluded that, 1) the effectiveness of cyber law enforcement in dealing with hoax news using UU ITE no. 19 of 2016 is still not maximized even though it is threatened with a sentence of six years and a fine of 1 billion rupiah. Factors affecting the effectiveness of the law must be reviewed from several aspects; (a) the legal factor itself, (b) the law enforcement officer factor, (c) the facilities and infrastructure factor, (d) the community factor, (e) the cultural factor. 2) Implementation of the Circular Letter of the Chief of Police No. SE/2/11/2021 related to the ITE Law which emphasizes restorative justice has not been able to minimize or reduce hoaxes because if the perpetrators just apologize, they will not be punished and the case is considered finished. The guidelines in No. SE/2/11/2021 have not answered the issue of hoaxes that lead to criminalization and have the potential to open new criminalization spaces for the interpretation of an act that is considered defamation. Keywords: Hoax, Law, Cyber